Artificial Means for Improving Human Motion - Diana Hodgins (Applied Bionics and Biomechanics)
This paper gives a brief description of some of the key ongoing product developments in Europe for medical implants. A range of medical systems that are currently being developed under European-funded programmes are briefly described. The first is an implant that helps people with ‘dropped foot’ improve their walking. Further research on body-worn inertial measuring systems (IMUs) and microsystems will extend the capabilities to other lower-limb and upper-limb applications in the future. Other medical systems being developed with the use of microsystems and nanotechnology include a system to aid deaf and blind people.